2016
DOI: 10.1016/j.bbmt.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytomegalovirus Reactivation on Relapse after Allogeneic Hematopoietic Stem Cell Transplantation in Pediatric Acute Leukemia

Abstract: Recent studies have demonstrated the protective effect of cytomegalovirus (CMV) reactivation against relapse after allogeneic hematopoietic stem cell transplantation (HSCT) for adult myeloid malignancies. We assessed the association of CMV reactivation, defined as the development of CMV antigenemia (at least 1 pp65 antigen-positive cell per 5.0 × 10(4) WBCs) within 100 days after HSCT, with the risk of relapse in 143 patients with pediatric acute leukemia. The median age at HSCT was 7 years, and underlying dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…Patients experiencing CMV reactivation among 674 allogeneic HSCT recipients were protected from leukemia relapse and experienced superior disease-free survival [24]. Similar findings were reported from a study involving 101 ALL and 42 AML pediatric patients [25]. In these patients, NK cells matured rapidly into cytotoxic CD56 dim KIR+ NKG2A- cells as a result of response to stimulatory signals provided by CMV.…”
Section: Nk Cells and Hematopoietic Stem Cell Transplantation For Leusupporting
confidence: 71%
“…Patients experiencing CMV reactivation among 674 allogeneic HSCT recipients were protected from leukemia relapse and experienced superior disease-free survival [24]. Similar findings were reported from a study involving 101 ALL and 42 AML pediatric patients [25]. In these patients, NK cells matured rapidly into cytotoxic CD56 dim KIR+ NKG2A- cells as a result of response to stimulatory signals provided by CMV.…”
Section: Nk Cells and Hematopoietic Stem Cell Transplantation For Leusupporting
confidence: 71%
“…Interestingly, when looking at the 85 patients in our cohort who had received an HSCT for a malignant disease, a tendency towards a lower relapse risk was seen in patients affected by viral infections. Several studies showed similar results for CMV, especially in acute myeloid leukemia (AML) patients [48][49][50], Auger et al for EBV and Nordlander et al for HSV infections [51,52]. The underlying mechanism of this relapse reduction remains unknown.…”
Section: Discussionmentioning
confidence: 82%
“…CMV + grafts showed a high presence of private clonotypes, probably due to TRG reshaping, indicating that the donor CMV status could be associated with AML outcome after HSCT. A beneficial effect of CMV reactivation after HSCT has been recently demonstrated, as several studies reported reduced risk of relapse in AML patients who develop CMV reactivation (55)(56)(57). Additionally, donor CMV positivity alone was also associated with a lower relapse rate after HSCT (58).…”
Section: Discussionmentioning
confidence: 95%